Registro civil das pessoas naturais: o ofício da cidadania como instrumento para a efetividade dos direitos fundamentais (perspectivas de novas atribuições) - Saliba, Patricia Gasperini Faria (2022)
How the State organizes its functions, duties-powers, has direct implications about how the interests of the collectivity will be met, within the possibilities of the best possible realization. The Brazilian Constitution of 1988 organized the provision of extrajudicial services to honor indirect management, in the same way as its article 236 recommends. It was a choice guided, basically, by the objective of combining efficiency, technical knowledge, division of responsibilities, and exemption of costs promoting the pluralization of the State in another aspect. To fulfill this aim, the activity was delegated to individuals, notaries, and registrars, who, under the supervision of the Judiciary Power, carry out their activities in favor and the interest of society. Using the hypothetical-deductive method, the main focus of this research is to demonstrate the work of civil registrars, which act as an instrument for the effectiveness of fundamental rights, as well as to promote reflection on perspectives in terms of new attributions. The main theme is explored, passing through subjects that are intertwined with the normal development of the craft, such as the secondary activity and how it is performed, its bases, principles, standardization, granting of gratuities, and the perspectives of services that can be carried out by the Civil Registry of Natural Persons, entitled by Law No. 13.484, of September 26, 2017, as Citizenship Office.